Antibiotic resistance genes (ARG) as environmental contaminants: occurrence in Cache La-Poudre River watershed and response to biological treatment - Pei, Ruoting, author; Pruden, Amy J., advisor (Colorado State University. Libraries, 2006)
In this study antibiotic resistance genes (ARG) were investigated as emerging environmental contaminants. The spread of ARG is of major concern because they are the agents that allow pathogenic microorganisms to become resistant to antibiotics, thus rendering antibiotics ineffective for fighting disease. ARG were quantified in various environmental compartments, which provided a means to assay the environmental impact of corresponding antibiotics in the environment, which originate from both human and agricultural sources. An initial baseline study was conducted and demonstrated a relationship between the number of ARG present in the sediments of the Cache La Poudre (Poudre) River and the relative levels of adjacent urban and agricultural activities. Five Poudre River sites of various urban and agricultural impacts were monitored for quantities of four ARG [tet(W), tet(O), sul(I), and sul(II)] on five sampling dates for over a one year period using quantitative real-time polymerase chain reaction. It was found that while a consistent spatial pattern was observed with the levels of ARG relating to the level of human and agricultural activity, there was no clear temporal pattern in the levels of ARG. It was also observed that dairy lagoon water had significantly higher concentrations of ARG than adjacent irrigation ditch water, which had greater concentrations than the neighboring Poudre River sediments, suggesting a potential pathway for the spread of ARG from farms to the river. To take a step toward minimizing the spread of the ARG from agricultural sources, the response of six ARG corresponding to three antibiotic classes (tetracycline, sulfonamide, and macrolide) to biological treatment was studied in anaerobic and aerobic lagoon water at ambient and reduced temperatures. It was found that tet(W), tet(O), sul(I), and sul(II) ARG responded differently to the different aerobic/anaerobic and temperature treatments. The two macrolide ARG, ereA and msrA, were present at very low levels and showed no response to any of the treatments. Overall, anaerobic treatment was the most effective for achieving final ARG levels that were equal to initial levels. No treatments reduced ARG below the initial levels, while some treatments resulted in higher ARG concentrations. This study is the first to quantitatively explore the levels of various ARG in environmental compartments and to investigate the effect of biological treatment. Future work is needed to further characterize ARG pathways and behavior in the environment and to explore alternative approaches for reducing ARG present in animal waste prior to land-application.
Keywords: environmental science; environmental engineering